The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000508653
|View full text |Cite
|
Sign up to set email alerts
|

Onset and Severity of Early Disruptive Behavioral Disorders in Treatment-Seeking Substance Use Disorder Patients with and without Attention-Deficit/Hyperactivity Disorder

Abstract: This study addressed the age of onset of conduct disorder (CD) and oppositional defiant disorder (ODD) in treatment-seeking substance use disorder (SUD) patients with and without adult attention-deficit/hyperactivity disorder (ADHD) and its association with early onset of SUD. Methods: We examined data from the 2nd International ADHD in Substance Use Disorders Prevalence Study, including 400 adults in SUD treatment from Puerto Rico, Hungary, and Australia. ADHD, SUD, and CD/ODD were assessed with the Conners A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the IASP study was expanded to Puerto Rico and South Africa (IASP-2). Details on study design and some of the data from the IASP-2 study are presented in this special issue of European Addiction Research [21, 22]. In the CASP study, we collected data with a novel continuous performance test [23] in SUD patients with and without ADHD.…”
Section: Ongoing Projectsmentioning
confidence: 99%
“…Furthermore, the IASP study was expanded to Puerto Rico and South Africa (IASP-2). Details on study design and some of the data from the IASP-2 study are presented in this special issue of European Addiction Research [21, 22]. In the CASP study, we collected data with a novel continuous performance test [23] in SUD patients with and without ADHD.…”
Section: Ongoing Projectsmentioning
confidence: 99%
“…Comorbidity between these disorders and SUD is not only common but is associated with increased addiction severity [14]. How they relate to nicotine addiction, also characterized by impulse control deficits, is of interest from a developmental perspective [32].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the DSM-5-based psychiatric interview, the diagnoses of the participants were as follows: 22.8% (79) schizophrenia and other disorders with psychosis, 34.7% (120) depressive disorder, 21.4% (74) disruptive behavior disorder, 7.5% (26) trauma and related disorder, 7.8% ( 27) bipolar disorder, 6.1% (21) anxiety disorder, 7.2% ( 25) eating disorder, 6.1% (21) somatic disorder, 13.0% (45) neurodevelopmental disorder, and 5.5% (20) obsessive-compulsive disorder (OCD) (Table II).…”
Section: Resultsmentioning
confidence: 99%
“…This situation poses a serious risk for delinquency and substance use behavior. 21 Longitudinal studies have found a strong positive relationship between the presence of externalizing behaviors in childhood and subsequent substance use in adolescence. 22 In a study that investigated the clinical characteristics of adolescents who were hospitalized in a child and adolescent substance treatment center, it was found that 80% of the cases had at least one comorbid psychiatric disorder, and of these, 46.3% were diagnosed with a conduct disorder.…”
Section: Discussionmentioning
confidence: 99%